Lithium increases proliferation of hippocampal neural stem/progenitor cells and rescues irradiation-induced cell cycle arrest in vitro - Zanni, Giulia; Di Martino, Elena; Omelyanenko, Anna; Andäng, Michael; Delle, Ulla; Elmroth, Kecke; Blomgren, Klas (Oncotarget, 2015)
Radiotherapy in children causes debilitating cognitive decline, partly linked to impaired neurogenesis. Irradiation targets primarily cancer cells but also endogenous neural stem/progenitor cells (NSPCs) leading to cell death or cell cycle arrest. Here we evaluated the effects of lithium on proliferation, cell cycle and DNA damage after irradiation of young NSPCs in vitro.NSPCs were treated with 1 or 3 mM LiCl and we investigated proliferation capacity (neurosphere volume and bromodeoxyuridine (BrdU) incorporation). Using flow cytometry, we analysed apoptosis (annexin V), cell cycle (propidium iodide) and DNA damage (γH2AX) after irradiation (3.5 Gy) of lithium-treated NSPCs.Lithium increased BrdU incorporation and, dose-dependently, the number of cells in replicative phase as well as neurosphere growth. Irradiation induced cell cycle arrest in G1 and G2/M phases. Treatment with 3 mM LiCl was sufficient to increase NSPCs in S phase, boost neurosphere growth and reduce DNA damage. Lithium did not affect the levels of apoptosis, suggesting that it does not rescue NSPCs committed to apoptosis due to accumulated DNA damage.Lithium is a very promising candidate for protection of the juvenile brain from radiotherapy and for its potential to thereby improve the quality of life for those children who survive their cancer.
Keywords: kultivované buňky; DNA Damage; Cobalt Radioisotopes; In Vitro Techniques; Animals, Newborn; apoptóza; průtoková cytometrie; Neural Stem Cells; paediatric oncology; chlorid lithný; hipokampus; poškození DNA; hippocampus; myši inbrední C57BL; kontrolní body buněčného cyklu; Mice; Cell Proliferation; záření gama; techniky in vitro; novorozená zvířata; Lithium Chloride; Cell Cycle Checkpoints; Flow Cytometry; Cells, Cultured; neurogeneze; ženské pohlaví; zvířata; Neurogenesis; lithium; radiotherapy; nervové kmenové buňky; myši; proliferace buněk; Hippocampus; Female; radioizotopy kobaltu; apoptosis; Mice, Inbred C57BL; Gamma Rays; Apoptosis; Animals